Implementasi Kebebasan Beragama di Tanggerang terhadap Etnis Umat Beragama Kristen - Osvaldo Antonio Linjewas; Abrar Rosyan Ali Barus; Nur Rahman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study examines the implementation of religious freedom in Indonesia, focusing on the case of the sealing of the POUK Tesalonika House of Prayer in Teluknaga, Tangerang Regency, in April 2026. This incident reflects the tension between administrative regulations, specifically the Building Permit, and the constitutional right to freedom of religion as guaranteed in Article 28E and Article 29(2) of the Constitution of the Republic of Indonesia. This study employs a normative legal method with legislative,conceptual, and case-based approaches. The analysis reveals that the sealing action fails to meet the principle of proportionality in administrative law, and results in legal discrimination that contradicts the principle of equality before the law and the spirit of Pancasila. These findings affirm that the right to worship is a non-derogable right that cannot be diminished by technical permitting regulations. Therefore, the state must prioritize a facilitative and protective approach in regulating places of worship, to guarantee freedom of religion and uphold Indonesia’s integrity as a democratic and tolerant rule of law state.